Web Untuk Deteksi Dini Tingkat Retardasi Down Syndrome Pada Anak - Christine Leonita; Nina Sevani (Maranatha University Press, 2015)
Down Syndrome is a condition of physical and mental development's retardation in children that caused by abnormalities in the development of the chromosome. However, behind the special needs held by children with Down syndrome, they have a chance to live like any other normal child.This study aims to create a web-base application that can assist parents to make early detection of the retardation level of Down Syndrome in children, as well as provide information about how to deal with Down Syndrome. One of the benefit of this application is to help parents who have Down syndromes children in order to make early treatment correctly. Other benefit for psychologist is to help them make notes about the progress of the Down syndromes patient. The results of the testing and evaluation declared that this web fit and feasible to detect the level of retardation in children with Down syndrome.Keywords: Down syndrome, detection, level of retardation, web